2010
DOI: 10.11606/issn.1679-9836.v89i2p115-123
|View full text |Cite
|
Sign up to set email alerts
|

Rastreamento da frequência de comportamentos sugestivos de transtornos alimentares na Universidade Positivo

Abstract: Objetivo: Rastrear a frequência de comportamentos sugestivos de transtornos alimentares em amostra de alunos de cursos pré-selecionados por sorteio da Universidade Positivo e com isso comparar a prevalência desses distúrbios alimentares entre os cursos selecionados e entre homens e mulheres, e confrontar com dados da literatura mundial. Métodos: Este é um estudo transversal no qual foram aplicadas as auto-escalas Bite (Teste de investigação Bulímica de Edimburgh) e EAT-26 (Teste de Atitudes Alimentares) em 463… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
11

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 16 publications
1
3
0
11
Order By: Relevance
“…Identifi ed in the population was a sub group with nutritional problems who showed a high risk of developing eating disorders by the presence of behavioural risk and therefore preventative measures are required. The rate of prevalence was 4% for high risk of eating disorder, as per scale EAT-26 and taking into account that a cut off point equal or above 21 points , similar results were found in other studies made in Brazilian students in the area of health using the same instrument (7) . However another research found 23.7% to 30.1% of occurrences of behavioural risk for eating disorders among academics exclusively of the female gender in the five regions of the country (6) .…”
Section: Debatesupporting
confidence: 87%
See 2 more Smart Citations
“…Identifi ed in the population was a sub group with nutritional problems who showed a high risk of developing eating disorders by the presence of behavioural risk and therefore preventative measures are required. The rate of prevalence was 4% for high risk of eating disorder, as per scale EAT-26 and taking into account that a cut off point equal or above 21 points , similar results were found in other studies made in Brazilian students in the area of health using the same instrument (7) . However another research found 23.7% to 30.1% of occurrences of behavioural risk for eating disorders among academics exclusively of the female gender in the five regions of the country (6) .…”
Section: Debatesupporting
confidence: 87%
“…Through this instrument an evaluation is made of the factors or behavioural risks for eating disorders, that are then used as problem indicators for a defi ned place and population (6) . Actually some research points to a bigger incidence of risk factors for eating disorders among young academics, principally for academics on courses in the area of health, in some of which physical appearance is very important, such as nutrition, physical education, nursing and medicine (7)(8)(9) . Inadequate eating behaviour is often present in students who have a disturbed relationship between body and food (6,10) and can be associated with factors such as changes in life style, psychological pressure and reduction of eating time available due to the curriculum structure and the time for study (7) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A literatura aponta que comportamentos de risco como perfeccionismo, prática de dietas restritivas, excesso de exercício físico, vômitos autoinduzidos e consumo de medicamentos diuréticos, laxantes e anorexígenos são estratégias presentes para controlar o peso corporal pelos jovens com sintomas sugestivos de TA [8][9][10][11] . Esses comportamentos têm sido observados em jovens universitários, principalmente em acadêmicos de cursos da área da saúde, entre eles Nutrição, Educação Física, Enfermagem e Medicina, os quais apresentam uma valorização da aparência física [12][13][14][15] .…”
Section: Introductionunclassified
“…Universitários que apresentam relação conturbada com o alimento e com o corpo possuem maior frequência de comportamento alimentar inadequado 16 , e esse fato pode estar associado a fatores como mudança no estilo de vida, pressão psicológica e diminuição no tempo disponível para alimentação em decorrência da estrutura curricular 14 .…”
Section: Introductionunclassified